The integrated incretin effect is reduced by both glucose intolerance and obesity in Japanese subjects - Hamasaki, Akihiro; Harada, Norio; Muraoka, Atsushi; Yamane, Shunsuke; Joo, Erina; Suzuki, Kazuyo; Inagaki, Nobuya (Frontiers in Endocrinology, 2024)
Introduction Incretin-based drugs are extensively utilized in the treatment of type 2 diabetes (T2D), with remarkable clinical efficacy. These drugs were developed based on findings that the incretin effect is reduced in T2D. The incretin effect in East Asians, whose pancreatic β-cell function is more vulnerable than that in Caucasians, however, has not been fully examined. In this study, we investigated the effects of incretin in Japanese subjects. Methods A total of 28 Japanese subjects (14 with normal glucose tolerance [NGT], 6 with impaired glucose tolerance, and 8 with T2D) were enrolled. Isoglycemic oral (75 g glucose tolerance test) and intravenous glucose were administered. The numerical incretin effect and gastrointestinally-mediated glucose disposal (GIGD) were calculated by measuring the plasma glucose and entero-pancreatic hormone concentrations. Results and discussion The difference in the numerical incretin effect among the groups was relatively small. The numerical incretin effect significantly negatively correlated with the body mass index (BMI). GIGD was significantly lower in participants with T2D than in those with NGT, and significantly negatively correlated with the area under the curve (AUC)-glucose, BMI, and AUC-glucagon. Incretin concentrations did not differ significantly among the groups. We demonstrate that in Japanese subjects, obesity has a greater effect than glucose tolerance on the numerical incretin effect, whereas GIGD is diminished in individuals with both glucose intolerance and obesity. These findings indicate variances as well as commonalities between East Asians and Caucasians in the manifestation of incretin effects on pancreatic β-cell function and the integrated capacity to handle glucose.